PD-L1 Is a Tumor Suppressor in Aggressive Endometrial Cancer Cells and Its Expression Is Regulated by miR-216a and lncRNA MEG3 - Xu, Daozhi; Dong, Peixin; Xiong, Ying; Chen, Rui; Konno, Yosuke; Ihira, Kei; Yue, Junming; Watari, Hidemichi (Frontiers in Cell and Developmental Biology, 2020)
Background: Poorly-differentiated endometrioid adenocarcinoma and serous adenocarcinoma represent an aggressive subtype of endometrial cancer (EC). Programmed death-ligand-1 (PD-L1) was known to exhibit a tumor cell-intrinsic function in mediating immune-independent tumor progression. However, the functional relevance of tumor cell-intrinsic PD-L1 expression in aggressive EC cells and the mechanisms regulating its expression remain unknown. Methods: PD-L1 expression in 65 EC tissues and 18 normal endometrium samples was analyzed using immunohistochemical staining. The effects of PD-L1 on aggressive EC cell growth, migration and invasion were investigated by cell functional assays. Luciferase reporter assays were used to reveal the microRNA-216a (miR-216a)-dependent mechanism modulating the expression of PD-L1. Results: Positive PD-L1 expression was identified in 84% of benign cases but only in 12% of the EC samples, and the staining levels of PD-L1 in EC tissues were significantly lower than those in the normal tissues. Higher PD-L1 expression predicts favorable survival in EC. Ectopic expression of PD-L1 in aggressive EC cells results in decreased cell proliferation and the loss of mesenchymal phenotypes. Mechanistically, PD-L1 exerts the anti-tumor effects by downregulating MCL-1 expression. We found that PD-L1 levels in aggressive EC cells are regulated by miR-216a, which directly targets PD-L1. We further identified a mechanism whereby the long non-coding RNA MEG3 represses the expression of miR-216a, thereby leading to increased PD-L1 expression and significant inhibition of cell migration and invasion. Conclusions: These results reveal an unappreciated tumor cell-intrinsic role for PD-L1 as a tumor suppressor in aggressive EC cells, and identify MEG3 and miR-216a as upstream regulators of PD-L1.